The Effect of Videoscribbe Sparkol on Students' Creative Writing Skill at Third Semester Students of English Education Study Program of Muhammadiyah Tangerang University - Wulandari, Ratih Ayu; Soraya, Kety; Astuti, Peni; Trikawati, Trikawati; Rosnaningsih, Asih (JEDLISH : Journal Of Education and English Language Teaching, 2022)
The purpose of this study was to determine the effect of using VideoScribe Sparkol on the English creative writing skills at the third semester students of the English Education Study Program of Muhammadiyah Tangerang University. This study used quantitative approach with Quasi-Experimental design method. The instrument used was essay writing tests. The results of the study showed that: (1) the results of the pre-test t-count 1.025 < t-table 2.000 or H0 was accepted, meaning that there was no difference in creative writing skills between the control class and the experimental class, (2) the results of the post-test t-count 2.161 > t-table 2.000 or H1 was accepted, meaning that there were differences in creative writing skills between the control class and the experimental class after being exposed to the VideoScribe Sparkol learning media. It could be concluded that by using VideoScribe Sparkol learning media, students were able to achieve maximum results in their creative writing scores because through this learning media, students could carry out creative and meaningful writing activities as well as increase their writing skills in general.